Transformasi Ritual Ngimbo Nineak menjadi Tari Ngimbo Nineak di Kota Sungai Penuh - Syafitri, Diana; Asriati, Afifah (Lembaga Yasin AlSys, 2025)
This study aims to describe the transformation of the Ngimbo Nineak ritual into the Ngimbo Nineak dance in Sungai Penuh City. A qualitative approach with a descriptive-analytical method was used, focusing on the original ritual and the dance form developed from this tradition. Data were collected through literature review, observation, interviews, and documentation, and analyzed through the stages of data collection, reduction, presentation, and conclusion drawing. The findings reveal that Ngimbo Nineak was originally a ritual performed by specific lineages with spiritual connections to their ancestors, particularly involving esoteric knowledge. The transformation into a dance was carried out by preserving the core meaning of the ritual while presenting it in a more communicative and publicly accessible performance art form. The Ngimbo Nineak dance represents the core activities of the ritual through elements such as storyline, symbolic movements, performers (dancers), accompanying music, costumes, properties, stage setup, and floor patterns. The study concludes that transforming the ritual into a dance is an adaptive form of cultural preservation that maintains the spiritual and symbolic values of the original tradition. Its implication is that the Ngimbo Nineak dance serves as a vital medium for sustaining cultural heritage and introducing it to younger generations within the framework of modern performing arts. Keywords: Cultural Transformation; Ngimbo Nineak Ritual; Traditional Dance; Performing Arts; Local Cultural Heritage